Treatment with Antithrombin or Thrombomodulin and Mortality from Heatstroke-Induced Disseminated Intravascular Coagulation: A Nationwide Observational Study - Ohbe, Hiroyuki; Isogai, Shunsuke; Jo, Taisuke; Matsui, Hiroki; Fushimi, Kiyohide; Yasunaga, Hideo (Seminars in Thrombosis and Hemostasis, 2019)
Heatstroke-induced disseminated intravascular coagulation represents potential targets for specific intensive treatments. However, the effect of antithrombin or thrombomodulin treatment remains uncertain. Using a large nationwide inpatient database in Japan, this study aimed to evaluate whether treatment with antithrombin or thrombomodulin could reduce mortality among patients with heatstroke-induced disseminated intravascular coagulation. Using the Japanese Diagnosis Procedure Combination inpatient database from April 2014 to March 2017, we identified heatstroke patients who developed disseminated intravascular coagulation. We allocated patients who started treatment with antithrombin or thrombomodulin within 2 days after admission to the treatment group and allocated others to the control group. A primary outcome was in-hospital mortality. We used a doubly robust analysis to ensure the robustness of our findings. We also conducted two sensitivity analyses for thrombomodulin versus others and antithrombin versus others. We identified 1,606 eligible patients during the 81-month study period. Of these, 556 (35%) received antithrombin or thrombomodulin. The doubly robust analysis demonstrated that in-hospital mortality was significantly lower among patients in the treatment group than among those in the control group (risk difference −6.5%; 95% confidence interval: −12 to −1.4%). In-hospital mortality was significantly lower in patients with thrombomodulin than in others (risk difference −5.5%; 95% confidence interval: −9.5 to −1.6%). There was no significant difference in in-hospital mortality between patients with antithrombin and others (risk difference −4.2%; 95% confidence interval: −9.3 to 0.9%). Treatment with recombinant human thrombomodulin may be associated with lower in-hospital mortality among patients with heatstroke-induced disseminated intravascular coagulation.
Keywords: heatstroke; disseminated intravascular coagulation; antithrombin; thrombomodulin